Sirtinol regulates the balance of Th17/Treg to prevent allograft rejection - Qing Ye (Cell & Bioscience, 2017)
Abstract Background Current immunosuppressive medications used after transplantation induce significant toxicity , and a new medication regimen is needed. Based on recent research, Sirt1 exerts a proinflammatory effect on the immune response. Sirtinol is a Sirt1 inhibitor, but its impact on allograft rejection and its molecular mechanisms of action have not yet been reported. Resluts In this study, we examined the effect of sirtinol on prolonging allograft survival in a mouse cervical heterotopic heart transplantation model. Based on an examination of the allograft, allografts from sirtinol-treated recipients show significantly lower levels of IL-17A expression and higher levels of Foxp3 expression. In vivo, sirtinol reduces the proportion of Th17 cells and increases the proportion of Treg cells in splenocytes from recipients. In vitro, sirtinol reduces the proportion of Th17 cells and decreases the expression of IL-17A and RORγt in an isolated CD4+ T cell population. Moreover, we identified synergistic effects of sirtinol and FK506 on prolonging allograft survival, and sirtinol synergizes with FK506 to promote Foxp3 expression. Conclusion Sirtinol, a Sirt1 inhibitor, may be a promising immunosuppressive drug to prevent the rejection reaction in combination with FK506.